Ultrasonic assisted oil extraction and biodiesel synthesis of spent coffee ground / Brandon Goh Han Hoe - Brandon Goh, Han Hoe (2019)
Biodiesel is a potential alternative fuel that can serve as a substitute for petroleum diesel due to its renewability, toxic free, sulphur free and better lubricity. Non-edible oils are studied as a potential biodiesel feedstock with focus on waste products as these can become value added products. Spent coffee ground (SCG) is studied as a potential source of oil for biodiesel production as an alternate waste utilisation instead of being treated as municipal waste. This study evaluates ultrasonic assisted oil extraction from SCG, followed by biodiesel conversion via transesterification. It was found that hexane was the most effective solvent for SCG oil extraction. Soxhlet extraction obtained maximum yield of 12.5% within 3 hours. The highest yield (14.52%) for ultrasonic extraction was obtained using 4mgL-1 hexane to SCG ratio, at 30% ultrasonic amplitude for 30 minutes. These improved results were due to the ultrasonic fragmentation of SCG cells, which enhanced interactions between oil and solvents. The infrared absorption spectrum analysis of SCG oil determined suitable functional groups for biodiesel conversion. Then, the SCG oil was successfully converted to biodiesel via ultrasonic assisted transesterification. The optimal fatty acid methyl ester (FAME) yield of 97.11% was achieved with molar ratio of methanol to SCG oil (30:1), 4 wt% potassium hydroxide concentration at 30% ultrasonic amplitude for 3 hours. The catalyst concentration showed the biggest change in terms of FAME. The SCG biodiesel has promising properties which adhere to the American Standards for Testing Materials (ASTM D6751) and European Union Standards for Biodiesel (EN 14214) standards but acidity was beyond the permissible limit. Due to the high acid value, it is recommended that SCG biodiesel be used as a blend with other commercially available biodiesel rather than a pure biodiesel. The high calorific value along with low viscosity, density and corrosion levels make SCG biodiesel an interesting option for biodiesel blending. In conclusion, ultrasonic assisted oil extraction and transesterification can be a feasible method for SCG biodiesel production. Detailed and in-depth information of the combustion characteristics and long term stability of the biodiesel can be further examined prior to the commercialization of SCG biodiesel.